A Model for sustainable biomass electricity generation in Bangladesh - Hossain, A. K. M. S. (Cranfield University, 2005)
Bangladesh, where only 20% of the total population are connected to grid electricity, has a promising scope to utilise biomass for decentralised electricity generation. In this study, sustainable biomass electricity generation model was developed for the country, by combining tech no-econometric and optimisation modelling techniques. The developed model addresses the biomass generation and availability, feasible technologies, cost and efficiency correlations, economic plant size, plant economics and sensitivity, and environmental and social impacts. In 2003, the national total annual available biomass energy potential in Bangladesh varies from 183.848 to 223.776 TWh. The feasible technologies are: gasification based ICE-generator, anaerobic digestion based ICE-generator and direct combustion based steam turbine or Stirling engine-generator. Correlations of capital investment costs and overall conversion efficiencies with the plant electricity generating capacity have been developed. Direct combustion technology shows the highest electricity generation potential of 20.21 TWh/year; followed by gasification, of 14.30 TWh/year. Economic radius of biomass collection and size of the plants has been determined for maximum profitability. The biomass electricity plants economics have been estimated and compared with the diesel and dual-fuelled plants. Analysis shows that, anaerobic digestion and gasification-based electricity generation plants are economically feasible. Biomass electricity plant is highly sensitive to changes in biomass price, selling price of electricity, investment cost, plant lifetime, conversion efficiency and operating hours. The employment of the biomass electricity instead of diesel generator saves significant amount of the greenhouse gas emissions. It creates more employment than conventional and presents other socio-economic benefits as well. Due to the combination of electricity generation potential, promising economics and low greenhouse gas emissions; gasification-based biomass electricity plant is recommended for the country. Biomass availability and plant economics vary between districts to districts. Computer programmes have been developed for district wise biomass electricity plant analysis.